2005
DOI: 10.1097/01.pcc.0000163673.40424.e7
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary resuscitation of a near-drowned child with a combination of epinephrine and vasopressin

Abstract: Bystander cardiopulmonary resuscitation, early and aggressive advanced life support, rewarming, and the combination of intravenous epinephrine and vasopressin were associated with sustained return of spontaneous circulation following hypothermic submersion-associated cardiac arrest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Human trials of medication use in accidental hypothermia do not exist, although case reports of survival with use of intra-arrest medication have been reported. 414,418,437 Given the lack of human evidence and relatively small number of animal investigations, the recommendation for administration or withholding of medications is not clear. It may be reasonable to consider administration of a vasopressor during cardiac arrest according to the standard ACLS algorithm concurrent with rewarming strategies (Class IIb, LOE C).…”
Section: Acls Modificationsmentioning
confidence: 99%
“…Human trials of medication use in accidental hypothermia do not exist, although case reports of survival with use of intra-arrest medication have been reported. 414,418,437 Given the lack of human evidence and relatively small number of animal investigations, the recommendation for administration or withholding of medications is not clear. It may be reasonable to consider administration of a vasopressor during cardiac arrest according to the standard ACLS algorithm concurrent with rewarming strategies (Class IIb, LOE C).…”
Section: Acls Modificationsmentioning
confidence: 99%
“…In the subgroup of patients with initial rhythm asystole, it improves the hospital discharge rate. Lienhart et al [19] and Sumann et al [20] reported that vasopressors could be useful to restore spontaneous circulation in hypothermic cardiac arrest patients prior to rewarming, thus avoiding prolonged mechanical CPR efforts or use of extracorporeal circulation. Compared with epinephrine, vasopressin exerts greater vasoconstriction in hypoxic and acidotic conditions [21].…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] On the other hand, the benefit of administering medications to treat VT/VF in severely hypothermic patients has not been established. Although there have been some case reports of improved survival with the use of medications in accidental hypothermia patients, 13,14 there have been no human interventional studies. In a systematic review of animal studies, vasopressor-like epinephrine or vasopressin improved the return of spontaneous circulation, but antiarrhythmic drugs such as amiodarone or bretylium did not result in an increased rate of return of spontaneous circulation.…”
Section: Discussionmentioning
confidence: 98%